Ineficiencia del uso de la renta de los recursos naturales a nivel regional en el Perú (2009-2022) - Campos Mendívil, Guadalupe (2023)
The growth of extractive economic activity has been reflected in the increase of its transfers to subnational governments, a process that allows governments to generate their own income to better spending; however, according to multiple authors, there is an inefficiency in its execution. This research seeks to estimate a quantitative and qualitative analysis of the behavior of capital spending for transfers of natural resources to regional governments to identify the main causes of its inefficiency, during the years 2009-2022. The main hypothesis is that regions tend to respond significantly more to government transfers than to transfers generated with their own resources (taxes, tributes, etc.), which leads to the suggestion that there is fiscal laziness within Peru's regions and a dependence on government transfers. For this, a Panel Data model was made to make the estimates at the quarterly level (2009-2022), added to different tests that help to choose between three possible proposed models: Pooled regression, random effects, and fixed effects. Among the results obtained, it was demonstrated that there is a better response to government transfer revenues than to the revenues generated by local and regional governments, highlighting the negative effect that these have on the efficiency of capital expenditure.